Functional studies and proteomics in platelets and fibroblasts reveal a lysosomal defect with increased cathepsin-dependent apoptosis in ATP1A3 defective alternating hemiplegia of childhood - Di Michele, Michela; Goubau, Christophe; Waelkens, Etienne; Thys, Chantal; De Vos, Rita; Overbergh, Lut; Schyns, Tsveta; Buyse, Gunnar; Casaer, Paul; Van Geet, Chris; Freson, Kathleen (Journal of proteomics, 2013)
Alternating hemiplegia of childhood (AHC) is a rare syndrome with repeated hemiplegic episodes, paroxysmal events and global neurological impairment. Recently, heterozygous de novo ATP1A3 missense mutations have been identified in AHC patients, but the underlying pathogenesis mechanism remains unknown. Mutation analysis of ATP1A3 in 9 unrelated AHC cases revealed mostly D801N or E815K variants. As platelets represent a good cellular model to study defects in neuropathologies, morphological and functional experiments were performed in these subjects. Platelets from the AHC patients presented with structural and functional abnormalities of granules positive for the lysosomal marker CD63. Similar structural granule abnormalities were detected in patients' fibroblasts. Proteomic analysis of platelets and fibroblasts showed a total of 93 differentially expressed proteins in AHC mainly involved in metabolism. Interestingly, 7 of these proteins were detected in both cell types, including the lysosomal protein cathepsin. AHC fibroblasts revealed significantly increased levels of activated cathepsin B, which induces a stronger activation of apoptosis. Our study is the first to link ATP1A3 defects in AHC to a platelet and fibroblast lysosomal defect with evidence of increased apoptosis. Further studies are needed to define how this lysosomal defect is related to decreased ATPase activity. Biological Significance Only recently, the genetic cause of AHC was identified as heterozygous ATP1A3 mutations, but the underlying pathophysiological mechanism still remains unknown. By performing functional, morphological and proteomic studies in AHC patients we found a structural and functional granule defect in AHC platelets and fibroblasts that was specifically found in granules positive for the lysosomal marker CD63. In particular, proteomics identified several differentially expressed proteins in fibroblasts and platelets from AHC cases that are predicted to have an important role in cell function and maintenance, a pathway typically attributed to lysosomes. The lysosomal protein cathepsin was found to be differentially expressed in both platelets and fibroblasts of AHC patients, inducing a stronger activation of mainly the intrinsic apoptosis. Despite the precise mechanism for the increased lysosomal cathepsin B-dependent apoptosis detected in AHC in relation to impaired ATP1A3 deserves further studies, we could here show some evidence for a defective regulation of apoptosis in AHC, a disease that still has no biochemical or neuroradiological parameters for diagnosis. [Display omitted] •AHC is caused by ATP1A3 mutations, but the biological defect still remains unknown.•We performed a morphological, functional and proteomic study in AHC patients.•AHC platelet/fibroblast granules positive for CD63 showed structural abnormalities.•Lysosomal cathepsin expression is altered in AHC, inducing activation of apoptosis.•This study is the first to link ATP1A3 defects to a lysosomal-like granule defect.